2000
DOI: 10.1128/jvi.74.2.676-683.2000
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Feline Immunodeficiency Virus (FIV) Soluble Factor(s) Produced from Antigen-Stimulated Feline CD8+T Lymphocytes Suppresses FIV Replication

Abstract: Feline immunodeficiency virus (FIV) causes AIDS-like symptoms in infected cats. Concanavalin A (ConA)-stimulated peripheral blood mononuclear cells (PBMC) from chronically FIV strain PPR-infected cats readily expressed FIV. In contrast, when PBMC from these animals were stimulated with irradiated, autologous antigen-presenting cells (APC), at least a 10-fold drop in viral production was observed. In addition to FIV-specific cytotoxic T lymphocytes, anti-FIV activity was demonstrated in the cell-free supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
(47 reference statements)
0
16
1
Order By: Relevance
“…on May 10, 2018 by guest http://jvi.asm.org/ responses were not measured in these studies, earlier reports imply that cell-mediated responses may be responsible for the observed survival of this one offspring (5,7,13,14). The finding that the dams became infected in both experiments where they nursed infected offspring is surprising and of great interest.…”
Section: Vol 78 2004 Highly Pathogenic Molecular Clone Of Fiv-c 8979contrasting
confidence: 44%
“…on May 10, 2018 by guest http://jvi.asm.org/ responses were not measured in these studies, earlier reports imply that cell-mediated responses may be responsible for the observed survival of this one offspring (5,7,13,14). The finding that the dams became infected in both experiments where they nursed infected offspring is surprising and of great interest.…”
Section: Vol 78 2004 Highly Pathogenic Molecular Clone Of Fiv-c 8979contrasting
confidence: 44%
“…Studies on the Petaluma isolate of FIV (FIV PET ) have shown that the human b-chemokines RANTES, MIP-1a, MIP-1b, and MCP-1 could not prevent infection of CrFK cells or T lymphocytes, whilst human SDF-1a could inhibit FIV PET infection of CrFK cells but not T cell lines, depending on the incubation conditions . In contrast, studies on another American isolate of FIV (FIV PPR ), which has 91% homology with FIV PET at the amino acid level, have revealed that human MIP-1a did suppress FIV replication in PBMC at a concentration of 500 ng/ml, whereas human SDF-1a used at the same concentration actually caused increased expression of FIV rather than suppression (Choi et al, 2000). Clari®ca-tion on the role of feline b-chemokines in CD8 T cell-mediated suppression of FIV replication will be reliant upon the availability of these recombinant feline proteins in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Following infection with FIV the host mounts a vigorous virus-speci®c cytotoxic T cell (CTL) response which precedes the development of virus-speci®c humoral immunity (Song et al, 1992;Beatty et al, 1996). In addition, non-cytolytic CD8 T cells, which suppress virus replication in a non-MHC-restricted manner by the secretion of soluble factors, have been described during acute and asymptomatic stages of FIV infection (Jeng et al, 1996;Hohdatsu et al, 1998;Veterinary Immunology and Immunopathology 85 (2002) 159±170 Flynn et al, 1999;Choi et al, 2000). Studies aimed at elucidating the immune correlates of vaccinal immunity have revealed that virus neutralising antibodies, virus-speci®c CTLs, and CD8 T cells capable of suppressing FIV replication, are all involved, either acting alone or in concert (Flynn et al, , 1999Hosie and Flynn, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In either case, the absence of this correlation suggests that other mechanisms could be used to resolve viral infection in the absence of a cytotoxic T-lymphoctye response, such as the noncytolytic mechanisms reported in the resolution of hepatitis B virus infection (28). In addition, both cytolytic and noncytolytic T cells are involved in the control of feline immunodeficiency virus infection (15,23). Interestingly, natural killer (NK) cell cytotoxic activity increased from 15 to 35% of specific lysis in T cells cultured from PRRSV-infected pigs and restimulated with PRRSV for 3 weeks (37).…”
Section: Vol 78 2004 Prrsv Load Is Independent Of T-cell Response Imentioning
confidence: 97%